Ejob Satisfaction and Turnover Intention of Nurses in Public Hospitals in Northern Negros Occidental - Sentinar, Amelyn A.; Arnibal, Sheila P. (Technium Social Sciences Journal, 2025)
The global nursing shortage is significantly exacerbated by nurse turnover, which refers to healthcare professionals leaving their current positions. The Philippines stands as a major global supplier of nurses, with a substantial 90% expressing intentions to work abroad, motivated by the pursuit of improved working conditions, job stability, opportunities for skill enhancement, and travel. This research sought to evaluate the job satisfaction and turnover intention among nurses in public hospitals across Northern Negros Occidental, Philippines, and to ascertain the degree of turnover intention across various demographic cohorts. Employing a quantitative, descriptive-correlational research design, this investigation involved 103 active, permanent, or contract-of-service nurses from public hospitals in Northern Negros, selected through a stratified random sampling method. Data collection was facilitated by an adapted and modified questionnaire, with the Turnover Intention Scale specifically deriving from Roodt and Chris (2004). Both descriptive analyses (using mean and standard deviation) and inferential analyses (employing Spearman Rank Correlation and Pearson Product Moment Correlation) were conducted. The findings indicated that nurses in Northern Negros’ public hospitals reported high levels of job satisfaction alongside moderate turnover intentions. While no significant association was observed between job satisfaction and age, sex, length of service, or source of income, a significant relationship was identified with civil status. Conversely, turnover intention exhibited no significant correlation with age, sex, civil status, length of service, or source of income. Notably, a critical finding established a significant relationship between job satisfaction and turnover intention.